Chromosome Genome Sequencing and Comparative Transcriptome-Based Analyses of Kloeckera apiculata 34-9 Unveil the Potential Biocontrol Mechanisms Against Citrus Green Mold - Tian, Zhonghuan; Du, Yujie; Yang, Fan; Zhao, Juan; Liu, Shuqi; Zhang, Deyao; Long, Chao-an (Frontiers in Microbiology, 2021)
Biological control is an environmentally friendly, safe, and replaceable strategy for disease management. Genome sequences of a certain biocontrol agent could lay a solid foundation for the research of molecular biology, and the more refined the reference genome, the more information it provides. In the present study, a higher resolution genome of Kloeckera apiculata 34-9 was assembled using high-throughput chromosome conformation capture (Hi-C) technology. A total of 8.07 M sequences of K. apiculata 34-9 genome was anchored onto 7 pesudochromosomes, which accounting for about 99.51% of the whole assembled sequences, and 4,014 protein-coding genes were annotated. Meanwhile, the detailed gene expression changes of K. apiculata 34-9 were obtained under low temperature and co-incubation with Penicillium digitatum treatments, respectively. Totally 254 differentially expressed genes (DEGs) were detected with low temperature treatment, of which 184 and 70 genes were upregulated and downregulated, respectively. Some candidate genes were significantly enriched in ribosome biosynthesis in eukaryotes and ABC transporters. The expression of gene Kap003732 and Kap001595 remained upregulated and downregulated through the entire time-points, respectively, indicating that they might be core genes for positive and negative response to low temperature stress. When co-incubation with P. digitatum, a total of 2,364 DEGs were found, and there were 1,247 upregulated and 1,117 downregulated genes, respectively. Biosynthesis of lysine and arginine, and phenylalanine metabolism were the highest enrichment of the cluster and KEGG analyses of the co-DEGs, the results showed that they might be involved in the positive regulation of K. apiculata 34-9 response to P. digitatum. The completeness of K. apiculata 34-9 genome and the transcriptome data presented here are essential for providing a high-quality genomic resource and it might serve as valuable molecular properties for further studies on yeast genome, expression pattern of biocontrol system, and postharvest citrus storage and preservation.